2005
DOI: 10.1002/art.20854
|View full text |Cite
|
Sign up to set email alerts
|

SLC22A4 polymorphisms implicated in rheumatoid arthritis and Crohn's disease are not associated with rheumatoid arthritis in a Canadian Caucasian population

Abstract: Objective Single‐nucleotide polymorphisms (SNPs) in the SLC22A4 gene encoding the organic cation transporter OCTN1 have been associated with rheumatoid arthritis (RA) in the Japanese population and with Crohn's disease in a Canadian cohort. The RA‐associated and Crohn's disease–associated SNPs include, respectively, an intronic variant (slc2F2) and an exonic variant (1672T). We used a case–control approach to investigate the prevalence of these variants in a Canadian RA cohort and to determine whether RA and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 18 publications
(29 reference statements)
3
29
1
Order By: Relevance
“…Interestingly, the Crohn's disease-associated CARD15 and SLC22A4/SLC22A5 alleles do not appear to confer risk for RA, at least in Caucasian populations (32,33), and the data reported here suggest that the PTPN22 1858T variant also is not involved in Crohn's disease susceptibility. These findings raise the possibility that Crohn's disease and psoriatic arthritis are genetically similar conditions, while RA is genetically distinct from these disorders and instead has genetic overlap with other conditions, such as lupus and type 1 diabetes.…”
Section: Discussionmentioning
confidence: 45%
“…Interestingly, the Crohn's disease-associated CARD15 and SLC22A4/SLC22A5 alleles do not appear to confer risk for RA, at least in Caucasian populations (32,33), and the data reported here suggest that the PTPN22 1858T variant also is not involved in Crohn's disease susceptibility. These findings raise the possibility that Crohn's disease and psoriatic arthritis are genetically similar conditions, while RA is genetically distinct from these disorders and instead has genetic overlap with other conditions, such as lupus and type 1 diabetes.…”
Section: Discussionmentioning
confidence: 45%
“…a British data derived from Barton et al (2004) b Canadian data derived from Newman et al (2005) c European data derived from Peltekova et al(2004) d Swedish data derived from Prokunina et al (2004) and Prokunina et al (2002) e European American data derived from Prokunina et al (2004) f Danish data derived from Nielsen et al (2003) g North American data derived from Begovich et al (2004) h North American data derived from Kyogoku et al (2004) i North Amerian data derived from Bottini et al (2004) j Japanese data from our group, reported by Suzuki et al (2003) k Japanese data derived from Yamazaki et al (2004) * P value calculated by Fisher's exact test: P < 0.01 ences in allele frequency less outstanding than L503F in SLC22A4/5, it was of note that PD-1.3A in PDCD1 and R620W in PTPN22 were only polymorphic in Caucasians and in the African-descent population, as for L503F in SLC22A4/5. Populations of African descent, Caucasians, and Japanese (an ethnic subgroup from fareast islands), should have different population histories of mutation, migration, isolation, and genetic drift, and there is no doubt that there should be substantial differences in allele frequencies among these ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, a genetic variant of the RUNX1 gene itself was also found to be implicated in RA susceptibility, where an intronic SNP, designated runx1, was strongly associated with RA risk (maximum OR 1.48, P = 0.00035, under a dominant model) . To date, the findings of Tokuhiro and colleagues have not been replicated in either Japanese or Caucasian populations Barton et al 2005b;Newman et al 2005;Martinez et al 2006b;Orozco et al 2006), while it is interesting to note that, in Caucasian populations, a nonsynonymous substitution (1672C [ T; rs1050152) causing an amino-acid change (L503F) in the SLC22A4 was proposed as a potential causal variant for Crohn's disease, a chronic inflammatory bowel disease with immunologically mediated processes (Fisher et al 2006).…”
Section: Introductionmentioning
confidence: 99%